Live-cell images of fluorescence recovery after photobleaching (FRAP) experiments in the strain expressing FgPin3-GFP. - Yakubu Saddeeq Abubakar (5558399) (2025)
Live-cell images of fluorescence recovery after photobleaching (FRAP) experiments in the strain expressing FgPin3-GFP.